2005
DOI: 10.1002/mc.20123
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TPA‐induced cyclooxygenase‐2 (COX‐2) expression by apigenin through downregulation of Akt signal transduction in human keratinocytes

Abstract: Apigenin is a nonmutagenic bioflavonoid that has been shown to be an inhibitor of mouse skin carcinogenesis induced by the two-stage regimen of initiation and promotion with dimethylbenzanthracene (DMBA) and 12-Otetradecanoylphorbol-13-acetate (TPA). These DMBA/TPA-induced squamous cell carcinomas overexpress cyclooxygenase-2 (COX-2). Cyclooxygenases are key enzymes required for prostaglandin (PG) synthesis, converting the arachidonic acid (AA) released by phospholipase A2 into prostaglandins. A large body of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 43 publications
3
49
1
Order By: Relevance
“…inhibitors against Erk1/2, p38 (SB203580 or SB202190), and JNK (JNK inhibitor II) at concentrations, which had been shown to be effective in keratinocytes (Park et al, 2005;Van Dross et al, 2005), we still observed a cytoprotective effect of KGF. These results demonstrate that neither MAPK signaling nor PI3K signaling is essential for the cytoprotective effect.…”
Section: Kgf Is Cytoprotective For Human Keratinocytes In Vitromentioning
confidence: 67%
“…inhibitors against Erk1/2, p38 (SB203580 or SB202190), and JNK (JNK inhibitor II) at concentrations, which had been shown to be effective in keratinocytes (Park et al, 2005;Van Dross et al, 2005), we still observed a cytoprotective effect of KGF. These results demonstrate that neither MAPK signaling nor PI3K signaling is essential for the cytoprotective effect.…”
Section: Kgf Is Cytoprotective For Human Keratinocytes In Vitromentioning
confidence: 67%
“…HaCaT cells, a spontaneously immortalized human keratinocyte cell line, were cultured as described previously (21). HaCaT cells were 85% to 90% confluent at the time of exposure to UVB or ''sham'' irradiation followed by treatment with 0, 10, or 20 Amol/L apigenin.…”
Section: Methodsmentioning
confidence: 99%
“…Apigenin treatment reduces the number and the size of skin tumors that develop in response to chemical carcinogen or UVB exposure via a mechanism that involves inhibition of ornithine decarboxylase activity (Wei et al, 1990). Apigenin also inhibits the TPA-dependent increase in c-jun and c-fos gene expression and tumor promotion in mouse skin (Huang et al, 1997c), and suppresses TPA-mediated COX-2 expression by blocking Akt signal transduction and arachidonic acid release in HaCaT cells (Van Dross et al, 2005).…”
Section: Apigeninmentioning
confidence: 99%